Metodología para el control de gestión y su incidencia en la producción y comercialización de la pequeña empresa Avícola Maratea - Lucas Lucas, Luigi Luciano (2019)
The research work carried out was aimed to develop a management control methodology, which allowed the translation and communication of the strategy of the small company Avícola Maratea to influence its production and marketing levels, where the types of research were applied: exploratory, descriptive, bibliographic, field, which allowed to obtain relevant information for its development. Likewise, the inductive, deductive, analytical synthetic, statistical, Delphi methods were used, which contributed to the deployment of the different stages of the proposed research. For the practical development of the project, information collection and processing, observation techniques, interviews, surveys, strategic cross-impact matrix, consensus technique, document review were used. A system of indicators was structured that, with the support of traffic lights, visualized the situation in which the Maratea poultry is located, at the end of the 1st half of 2019, where it was observed that in the Financial and Internal Customer perspectives good results were displayed when obtaining indicators in a favorable situation such as Liquidity, Solvency, Indebtedness, Productivity of the worker and Absenteeism rate of the working day. The Client and Internal Processes perspectives on the other hand presented indicators in an unfavorable situation in the indicators Number of orders fulfilled, level of production, Customer retention and Revenue by groups of clients. In this way the applicability of the proposal made was demonstrated.